Investigation of methods for extraction of bacterial DNA metagenome from goat rumen - Giang, Lê Ngọc; Ly, Lưu Hàn; Phương, Nguyễn Mai; Lâm, Lê Tùng; Huyền, Đỗ Thị; Nguyệt, Phùng Thu; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2018)
Microorganisms, particularly bacteria, in the ruminant's rumen are valuable genetic resources that many scientists interested in. In recent years, the application of next-generation sequencing technologies allows direct decoding an extracted DNA metagenome in each ecological community without culture, increasing the efficiency of exploiting interested genes. Notably, the quantity and quality of extracted DNA play an important role in getting a reliable metagenome database. In this study, DNA metagenome from goat rumen fluid was extracted by five different methods RBB (repeated bead beating plus column), RBBC (repeated bead beating), PSP1, PSP2 (PSP®Spin Stool DNA Kit, protocol 1, 2, Germany) và QIA (QIAamp® DNA Stool Mini Kit, Germany). The results showed that DNA metagenome obtained by all methods had A260/280 greater than 1.8. DNA extracted by the RBB method had high DNA concentration but low A260/230 values (less than 1.4) and still contained Taq polymerase inhibitor. After purifying by QIA column, A260/230 values of RBB-extracted DNA significantly increased up to 2.0 and Taq polymerase inhibitor in samples were removed. However, the concentrations decreased by 57% that nearly equivalent to concentration of DNA metagenome obtained by QIA. The method using PSP®Spin Stool DNA kit produced the highest DNA concentrations (from 149.7 to 195.5 ng/µl) with A260/280 ratios of 1.9 and A260/230 ratios of 1.8 to 1.9. Morever, this method was able to remove polymerase inhibitor and be performed on short time. Therefore, the PSP®Spin Stool DNA kit is a suitable method for DNA metagenome extraction of bacteria from goat rumen. DNA obtained by this method fulfilled all criteria about quality and concentration for sequencing by next-generation sequencing Illumina.